Isothermal transport properties and majority-type defects of BaCo0.70Fe0.22Nb0.08O3−δ. Issue 4 (11th December 2014) - Lee, Taewon; Cho, Deok-Yong; Kwon, Hyung-Soon; Yoo, Han-Ill
Abstract : The increase in Onsager coefficients L ii of mobile O 2− and L hh of h + with oxygen activity indicates the majority type disorders to be oxygen interstitials and holes h˙. An inflection in log L hh vs. log a O2 suggests the presence of two types of hole carriers, one itinerant and the other trapped. Abstract : (Ba, Sr)(Co, Fe)O3− δ based mixed conducting oxides, e.g. (Ba0.5 Sr0.5 )(Co1− x Fe x )O3− δ and Ba(Co0.7 Fe0.3− x Nb x )O3− δ, are promising candidates for oxygen permeable membranes and SOFC cathodes due to their excellent ambipolar conductivities. Despite these excellent properties, however, their mass/charge transport properties have not been fully characterized and hence, their defect structure has not been clearly elucidated. Until now, the majority types of ionic and electronic defects have been regarded as oxygen vacancies and localized holes. Holes, whether localized or not, are acceptable as majority electronic carriers on the basis of the as-measured total conductivity, which is essentially electronic, and electronic thermopower. On the other hand, the proposal of oxygen vacancies as majority ionic carriers lacks solid evidence. In this work, we document all the isothermal transport properties of Ba(Co0.70 Fe0.22 Nb0.08 )O3− δ in terms of a 2 × 2 Onsager transport coefficient matrix and its steady-state electronic thermopower against oxygen activity at elevated temperatures, and determine the valences of Co and Fe via soft X-ray absorption spectroscopy. It turns out that the ionic and electronic defects in majority should be oxygen interstitials and at least two kinds of holes, one free and the other trapped. Furthermore, the lattice molecule should be Ba(Co0.7 Fe0.3− x Nb x )O2+ δ, not Ba(Co0.7 Fe0.3− x Nb x )O3− δ, to be consistent with all the results observed.